Inovasi Teknologi dalam Mendukung Penerapan Regulasi Manajemen Keselamatan Proses dan Pengelolaan Lingkungan - Marwaji, Marwaji; Situmorang, Marningot Tua Natalis; Kholil, Kholil (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Technological advances have a crucial role in supporting the implementation of process safety regulations and environmental management in the industrial sector. Technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and Big Data have contributed significantly to improving work safety and reducing negative impacts on the environment. With this technology, monitoring can be done in real-time, predictive analysis becomes more accurate, and decision making takes place more quickly and efficiently. However, its implementation in Indonesia still faces various challenges, including high investment costs, limited infrastructure, and a lack of skilled workers in this field. In addition, although regulations regarding process safety and environmental management in Indonesia are quite clear, the main challenge lies in consistency in implementation and enforcement. This article examines the role of technological innovation in supporting regulations, the obstacles faced in its implementation, and provides recommendations for optimizing the use of technology in creating a safer and more sustainable industrial environment.